Neonatal safety in intensive care conducted by the nursing team: narrative review (Research, Society and Development, 2022)
Objective: to analyze through the literature, the safety of neonates under intensive care governed by the nursing team. Methods: narrative review, carried out in the LILACS, SciELO and BDENF databases, based on studies published between 2015 and 2020. Results: the findings of this study made it possible to assimilate the reality of the nursing team and the needs of neonates and patients under care intensive care for the safety of the neonate. Therefore, it was possible to build knowledge about nursing care and we observed that the nursing team understands the importance of communication to ensure the safety of newborns, however, this communication is not effective and the consolidation of the neonatal safety culture presents several difficulties. Conclusion: this study allowed the elaboration of reflections that were not limited to describing the observed facts.